Combined spectroscopic and molecular docking study on the pH dependence of molecular interactions between β-lactoglobulin and ferulic acid. (April 2020) - Abdollahi, Kourosh; Ince, Cameron; Condict, Lloyd; Hung, Andrew; Kasapis, Stefan
Abstract: Interactions between β-lactoglobulin and ferulic acid were investigated at ambient temperature in relation to the dimer and monomer forms of the protein at pH 7.3 and 2.4, respectively. To this end, molecular dynamics (MD) simulations and a variety of spectroscopic methods were employed. Circular dichroism (CD) and Fourier transform infrared (FTIR) analysis indicate that the secondary structure of the protein is altered upon complexation, suggesting molecular interactions do occur in both the monomer and dimer forms. However, UV–vis measurements of β-lactoglobulin remain constant upon complexation with ferulic acid, indicating that interactions are non-covalent in nature and are likely stabilised by hydrophobic forces and hydrogen bonds. Fluorescence quenching confirms the presence of a binding state, with the monomeric complex producing a stronger dissociation constant than the dimeric counterpart. Docking studies and MD simulations indicate that the preferred binding site in the dimer form (pH 7.3) lies at the interface of the two monomers. In contrast, the preferred binding site for the monomer form (pH 2.4) lies within the calyx shaped β-barrel structure and is stabilised by hydrogen bonds and π - alkyl interactions. Graphical abstract: Image 1 Highlights: PH affects the binding site and strength of ferulic acid – β-lactoglobulin interaction. Binding affinity was found to be higher when β-lactoglobulin was in monomer form. The binding site in the dimer form lies at the interface of the two monomers. The binding site in the monomer form lies within the calyx shaped β-barrel.